The Relationship Between Husband's Support And Antenatal Care Visits At Puskesmas Tegalrejo Yogyakarta - Mita Febriani; Rosmita Nuzuliana (CV. ITTC INDONESIA, 2025)
Husband's support is an essential factor that influences pregnant women's adherence to attending Antenatal Care (ANC) visits. Husbands who provide emotional, informational, and instrumental support can increase a mother's motivation to undergo regular pregnancy check-ups. Regular ANC visits are crucial for monitoring maternal and fetal health and for early detection of potential pregnancy complications. However, many pregnant women do not attend ANC visits as recommended due to a lack of support from their partners. This study employed a quantitative method with a cross-sectional design. The study sample consisted of 53 third-trimester pregnant women selected using accidental sampling. Data were collected through a validated and reliable questionnaire. Data analysis was conducted using the chi-square test to examine the relationship between the independent variable (husband's support) and the dependent variable (ANC visits). The results showed that most respondents had moderate (45.3%) and low (41.5%) levels of husband support. Additionally, only 45.3% of respondents regularly attended ANC visits. Statistical analysis indicated a significant relationship between husband's support and pregnant women's adherence to ANC visits (p < 0.05). The study concludes that higher levels of husband support increase the likelihood of pregnant women attending ANC visits regularly. Therefore, family-based interventions involving husbands in maternal health education programs should be enhanced to improve ANC coverage